Territorial defence of the Republic of Slovenia - Kladnik, Tomaž (Studia Historica Slovenica, 2009)
Within two years, that is from April 1990 until April 1992, and after decades that passed from General Maister establishing the Sloveian army, and later unsuccessful similar attempts of the Slovenian partisan and Slovenian national army, the Slovenian Armed Forces were established. These were transformed from second-class reserve armed forces into modern defence forces in a critical and, for the developments of the Slovenian nation, crucial moment
Keywords: obrambna politika; Slovenija; slovenska vojska; teritorialna obramba